Application of ozone in post-harvest conservation of orange (Citrus sinensis) in La Troncal, Ecuador - Morán-Sánchez , N. L.; Castro-García , A. I.; Maliza-Yazuma , M. J.; Vargas-Guillén , P. I.; Cajamarca-Méndez , W. S. (Peruvian Agricultural Research, 2026)
Objective: To evaluate the eﬀect of ozone concentration and exposure time on oranges (Citrus sinensis) through experimental methods aimed at reducing the incidence of phytopathogenic fungi and extending their shelf life during storage. Methodology: A total of 384 oranges were collected and stored in a warehouse, forming 32 experimental units. A completely randomized design was used, assessing eight treatments: six corresponding to combinations of two factors, along with two control treatments. Factor A consisted of three liquid-ozone doses (1, 2, and 3 ppm), while Factor B involved the contact time with the fruit (10 and 20 minutes). Among the controls, one was a conventional treatment with sodium hypochlorite and the other an absolute control. The evaluated variables included pH, °Brix, incidence, and severity. Data were statistically analyzed using analysis of variance (ANOVA) and Tukey's test (p < 0.05). Results: The untreated control showed the highest values for pH, incidence, and severity. Ozone doses consistently reduced these variables, particularly 1 ppm applied for 10 minutes, while the remaining treatments presented slight and consistent diﬀerences. Severity, as deﬁned in the study, showed variations ranging from 11.3% to 17.7% in the factorial treatments, 23.2% in the absolute control, and 10.9% in the conventional treatment with sodium hypochlorite. Conclusions: Ozone application decreases pH, incidence, and severity compared to the untreated control. Diﬀerences among doses were small, but 1 ppm for 10 minutes produced the most pronounced eﬀects, even outperforming the conventional sodium hypochlorite treatment. Overall, ozone improved all evaluated conditions relative to the controls.